ANALISIS KETIMPANGAN PEMBANGUNAN SEKTOR DI PROVINSI SULAWESI SELATAN PADA TAHUN 2011-2015 - Ikrar Mallarangang (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
The aims of this research are(1) to find out the level of imbalance of agriculture sector in South Celebes province in 2011-2015. (2) to know the level of imbalance of industrial sector in South Celebes province in 2011-2015 and (3) to know the level of imbalance of other service sector in south sulawesi province in 2011-2015. The technique used to obtain the required data in this research is the documentation technique. To achieve the objectives and answer the problems that have been set, then used two kinds of data analysis methods, namely williamson index analysis, and theil index. the results show that: (1) based on williamson index analysis, the level of inequality that occurs is above zero, indicating inequality that occurred in South Celebes province during the period of 2011-2015 has increased, (2) based on the theil index analysis showed that there has been a very high inequality in South Celebes The theil index value during the period 2011-2015 shown an imbalance for the industrial sector, which is much higher than the agricultural sector, forestry and fisheries with other services, and this should be immediately addressed by the goverment.